2008
DOI: 10.1158/1078-0432.ccr-08-0320
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognostic Impact of FoxP3+ Regulatory T Cells in Human Gliomas

Abstract: Purpose: The incidence of regulatory T cells (Treg) in intrinsic central nervous system malignancies is unknown. Immunotherapeutic approaches that inhibit the Treg population may be limited to a subset of patients with gliomas. Our hypothesis is that only the most malignant gliomas have a prominent glioma-infiltrating Treg population that contributes to the immunosuppressive biology and that the presence of Tregs is a negative prognostic variable. Experimental Design: We measured the incidence of Tregs in 135 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
234
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(262 citation statements)
references
References 36 publications
13
234
2
7
Order By: Relevance
“…Heimberger et al (22) and Grabenbauer et al (23) investigated local tumor-infiltrating lymphocytes using tissue microarrays. Their conclusions, however, were conflicting, despite their studies being performed under almost identical conditions and using identical protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Heimberger et al (22) and Grabenbauer et al (23) investigated local tumor-infiltrating lymphocytes using tissue microarrays. Their conclusions, however, were conflicting, despite their studies being performed under almost identical conditions and using identical protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have shown greater immunosuppressive activity of T regs associated with CNS tumors (31)(32)(33). The transcription factor Foxp3 plays a crucial role in immune homeostasis and T reg development (34)(35)(36), as demonstrated by the dramatic autoimmune phenotype of the Foxp3 forkhead domain-deficient Scurfy mouse (37), and autoimmune disease in humans bearing Foxp3 mutations known as immunodysregulation polyendocrinopathy enteropathy X-linked syndrome.…”
mentioning
confidence: 97%
“…7 Regulatory T cells have recently been shown to play an important role in the progression of a variety of different neoplasms, 74 including gliomas. 30,33 Small numbers of FoxP3 þ cells were documented in a subset of the canine meningiomas in this study, suggesting that Tregs may be playing a role in tumor escape from the immune system in these patients.…”
Section: Discussionmentioning
confidence: 60%
“…32 Populations of Tregs have been shown to contribute to immune escape in a variety of cancers, 74 and recent studies have also shown these cells in human brain tumors. 30,33 Toll-like receptors (TLRs) on the surface of immune cells recognize a variety of microbial molecular patterns, and they initiate immune and inflammatory responses through several signal transduction pathways. For example, TLR4 recognizes lipopolysaccharide (LPS), and TLR9 recognizes unmethylated cytosine-guanine dinucleotide (CpG) motifs characteristic of bacteria.…”
Section: Cd25mentioning
confidence: 99%